Surface modification method of environment-friendly calcium carbonate powder

Through the surface modification method of plant-source coupling agent and water-based treatment agent, the problem of insufficient hydrophilicity and dispersion of traditional calcium carbonate powder is solved, which significantly reduces environmental pollution and improves the dispersion and stability of the material.

CN119410174APending Publication Date: 2025-02-11HENAN SILICON JIUHUA INNOVATION TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411661754.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

During the application process, traditional calcium carbonate powder has problems such as poor hydrophilicity, insufficient dispersion and low surfactivity, which leads to limited application in aqueous systems or organic systems. In addition, traditional modification methods use organic solvents and chemical reagents. , leading to environmental pollution and health risks.

Method used

The surface modification is carried out by plant-source coupling agent and water-based treatment agent. Through ultrasonic dispersion, acidic pretreatment, coupling layer formation and cross-linking stable treatment, a multi-layer modified structure is formed, which significantly improves the dispersion of calcium carbonate powder and Hydrophilicity.

Benefits of technology

It significantly reduces environmental pollution during the production process, improves the dispersion and hydrophilicity of calcium carbonate powder in aqueous matrix, reduces particle agglomeration, and enhances the chemical stability and application performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119410174A_ABST
    Figure CN119410174A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of calcium carbonate powder modification, and provides a surface modification method of environment-friendly calcium carbonate powder. The method comprises the following steps: S1, pretreating calcium carbonate powder, and removing impurities and enhancing surface activity through ultrasonic dispersion and acidic pretreatment; s2, mixing a plant source coupling agent with deionized water according to a ratio of 1: 10, heating to 30-50 DEG C, and adjusting the pH value to 5.0-6.0 to form a coupling solution; s3, stirring and mixing the pretreated calcium carbonate powder with a coupling solution according to a ratio of 1: 1; s4, the modified calcium carbonate powder is washed with deionized water until washing liquor is colorless, redundant coupling solution is removed, the calcium carbonate powder is placed in a drying oven to be dried, and a tannic acid coupling layer is stably attached. The plant source coupling agent and the water-based treating agent are adopted to effectively replace an organic solvent coupling agent commonly used in traditional modification, emission of volatile organic compounds is reduced, environmental pollution in the production process is remarkably reduced, the requirements of environmental protection laws and regulations and sustainable development are met, and negative effects on an ecological system are remarkably reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of calcium carbonate powder modification, in particular to a surface modification method of environmentally friendly calcium carbonate powder. Background Art

[0002] As an important inorganic filler, calcium carbonate powder is widely used in many industries such as coatings, plastics, rubber, papermaking, medicine and construction. Traditional calcium carbonate powder has problems such as poor hydrophilicity, insufficient dispersibility and low surface activity during application, which limits its application in aqueous or organic systems. In addition, unmodified calcium carbonate particles tend to agglomerate in composite materials, affecting the mechanical properties and processing properties of the material.

[0003] In order to improve the dispersibility and hydrophilicity of calcium carbonate powder, coupling agents are usually used in the prior art to modify the surface of calcium carbonate. Traditional surface modification methods usually use organic solvents and chemical reagents such as silane coupling agents and titanate coupling agents. Although these reagents can effectively improve the dispersibility and surface affinity of calcium carbonate, the emission of volatile organic compounds (VOCs) during their use is high, which is easy to cause harm to the environment and human health, and the processing cost is high, which does not meet the requirements of green environmental protection.

[0004] With the increasingly stringent environmental regulations and the increasing awareness of ecological environmental protection, the development of low-pollution, green and environmentally friendly calcium carbonate modification methods has become a research hotspot. At present, there have been some explorations of green modification methods, such as the use of water-based systems or plant-based materials for modification to replace traditional organic solvents. However, these methods still have deficiencies in hydrophilicity, water resistance and chemical stability, and the effect and stability in practical applications need to be further improved. Summary of the invention

[0005] In view of the shortcomings of the prior art, the present invention provides a surface modification method for environmentally friendly calcium carbonate powder, which solves the problems of serious environmental pollution, insufficient hydrophilicity and dispersibility in the calcium carbonate modification method.

[0006] To achieve the above objectives, the present invention is implemented through the following technical scheme: a surface modification method of environmentally friendly calcium carbonate powder, comprising the following steps;

[0007] S1. Pre-treating calcium carbonate powder to remove impurities and enhance surface activity by ultrasonic dispersion and acid pre-treatment;

[0008] S2, mixing the plant-derived coupling agent with deionized water at a ratio of 1:10, heating to 30°C-50°C, and adjusting the pH to 5.0-6.0 to form a coupling solution;

[0009] S3, stirring and mixing the pretreated calcium carbonate powder with the coupling solution at a ratio of 1:1;

[0010] S4, washing the modified calcium carbonate powder with deionized water until the washing solution is colorless, removing excess coupling solution, and drying the calcium carbonate powder in an oven to allow the tannic acid coupling layer to be stably attached;

[0011] S5, performing cross-linking stabilization treatment on the calcium carbonate powder after the initial modification;

[0012] S6, mixing the water-based treatment agent with deionized water at a ratio of 1:10, and controlling the temperature at 25° C.-40° C. to form a water-based treatment solution;

[0013] S7, slowly adding the cross-linked calcium carbonate powder into the water-based treatment solution and stirring to form a water-based protective layer;

[0014] S8. Dry, control the particle size and package the calcium carbonate powder after secondary modification to obtain environmentally friendly modified calcium carbonate powder.

[0015] Preferably, the step S1 specifically includes:

[0016] S1.1, grind the calcium carbonate powder to control the particle size to 5μm-15μm;

[0017] S1.2, mix calcium carbonate powder with deionized water in a ratio of 1:5;

[0018] S1.3, placing the mixed solution into an ultrasonic dispersion device at a frequency of 20kHz-50kHz and a power of 100W-200W for 15min-20min to evenly disperse the calcium carbonate powder and remove surface impurities;

[0019] S1.4. Filter the dispersed calcium carbonate powder using a vacuum filter to remove excess water;

[0020] S1.5, adding citric acid to deionized water, adjusting the pH of the solution to 4.5-5.5, to obtain an acidic solution;

[0021] S1.6. Slowly add the cleaned calcium carbonate powder into the acidic solution and stir at 200-400 rpm for 10-15 min at room temperature;

[0022] S1.7, wash the pretreated calcium carbonate powder with deionized water several times until the pH is neutral, and then perform vacuum filtration;

[0023] S1.8. Place the calcium carbonate powder in an oven at 50℃-70℃ and dry it for about 4h-6h.

[0024] Preferably, the plant-derived coupling agent in step S2 is tannic acid.

[0025] Preferably, in step S3, the stirring and mixing temperature is controlled at 30° C.-50° C., and the stirring time is controlled at 20 min-40 min.

[0026] Preferably, in step S4, the drying temperature is controlled at 60° C.-70° C., and the drying time is controlled at 5 h-7 h.

[0027] Preferably, the step S5 specifically includes:

[0028] S5.1, mixing citric acid with deionized water in a ratio of 0.1:100 to obtain a sodium citrate solution;

[0029] S5.2, adding dry calcium carbonate powder to the sodium citrate solution, stirring at 25°C-40°C for 20min-40min, so that the coupling layer and the sodium citrate undergo a cross-linking reaction;

[0030] S5.3, wash the calcium carbonate powder with deionized water 2-5 times to remove unreacted sodium citrate;

[0031] S5.4. Place the calcium carbonate powder in an oven to dry, and control the drying temperature at 50°C-70°C to ensure the stability of the cross-linking layer.

[0032] Preferably, the water-based treatment solution in step S7 is polyethylene glycol.

[0033] Preferably, in step S7, the stirring time is controlled at 30 min-90 min, the temperature is controlled at 25° C.-40° C., and 5%-15% sodium citrate is added as a secondary cross-linking agent during the stirring process.

[0034] Preferably, in step S7, the calcium carbonate powder is washed 2-5 times with deionized water, and the modified calcium carbonate powder is collected by vacuum filtration.

[0035] Preferably, in step S8, the drying temperature is controlled at 50° C.-70° C., the drying time is controlled at 6 h-10 h, and screening is performed after drying to control the particle size at 5 min-10 min.

[0036] The present invention provides a surface modification method for environmentally friendly calcium carbonate powder, which has the following beneficial effects:

[0037] 1. The present invention adopts plant-derived coupling agents and water-based treatment agents to effectively replace the organic solvent coupling agents commonly used in traditional modifications, reduce the emission of volatile organic compounds, significantly reduce environmental pollution in the production process, comply with environmental protection laws and regulations and the requirements of sustainable development, and significantly reduce the negative impact on the ecosystem.

[0038] 2. The present invention significantly improves the dispersibility of calcium carbonate powder in aqueous matrix through surface modification. The multi-layer modified structure reduces the tendency of particles to agglomerate, making the particles more evenly distributed in aqueous solution. In the application of water-based coatings and plastic composite materials, this modification greatly improves the dispersion effect of fillers and reduces stratification and sedimentation.

[0039] 3. After modification by using a plant-derived coupling agent, hydrophilic groups such as hydroxyl and carboxyl groups are introduced to the surface of the calcium carbonate powder, which makes the modified calcium carbonate powder have better affinity with the aqueous matrix. The contact angle test data verifies that the modified calcium carbonate powder exhibits significant hydrophilicity. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 The present invention is a flow chart of the method. DETAILED DESCRIPTION

[0041] The following will be combined with the drawings in the specification of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0042] Please see attached Figure 1 , an embodiment of the present invention provides a surface modification method of environmentally friendly calcium carbonate powder, comprising the following steps;

[0043] S1. Pre-treating calcium carbonate powder to remove impurities and enhance surface activity by ultrasonic dispersion and acid pre-treatment;

[0044] S2, mixing the plant-derived coupling agent with deionized water at a ratio of 1:10, heating to 30°C-50°C, and adjusting the pH to 5.0-6.0 to form a coupling solution;

[0045] S3, stirring and mixing the pretreated calcium carbonate powder with the coupling solution at a ratio of 1:1;

[0046] S4, washing the modified calcium carbonate powder with deionized water until the washing solution is colorless, removing excess coupling solution, and drying the calcium carbonate powder in an oven to allow the tannic acid coupling layer to be stably attached;

[0047] S5, performing cross-linking stabilization treatment on the calcium carbonate powder after the initial modification;

[0048] S6, mixing the water-based treatment agent with deionized water at a ratio of 1:10, and controlling the temperature at 25° C.-40° C. to form a water-based treatment solution;

[0049] S7, slowly adding the cross-linked calcium carbonate powder into the water-based treatment solution and stirring to form a water-based protective layer;

[0050] S8. Dry, control the particle size and package the calcium carbonate powder after secondary modification to obtain environmentally friendly modified calcium carbonate powder.

[0051] Specifically, the calcium carbonate powder is preliminarily ground to control its particle size within the range of 5μm-15μm to ensure the uniformity of the particles, and the ground calcium carbonate powder is mixed with deionized water at a ratio of 1:5. The mixed solution is placed in an ultrasonic dispersion device and treated at a frequency of 20kHz-50kHz and a power of 100W-200W for 15-20min to evenly disperse the calcium carbonate particles, remove surface impurities, increase the particle spacing, and reduce agglomeration. The dispersed calcium carbonate powder is vacuum filtered to remove excess water for subsequent acid treatment, and an appropriate amount of citric acid is added to the deionized water to adjust the solution pH to 4.5-5.5 to form an acidic solution. Slowly add the cleaned calcium carbonate powder to the acid solution, stir at 200rpm-400rpm for 10-15min at room temperature, remove the alkaline impurities remaining on the surface through the action of the acid and introduce active groups such as carboxyl and hydroxyl groups, wash the pretreated calcium carbonate powder with deionized water for multiple times until the washing liquid is neutral, filter and dry in an oven at 50℃-70℃ for 4-6h to make the calcium carbonate powder reach a low-humidity state, ensuring that its surface is clean and has good activity;

[0052] Tannic acid is used as a plant-based coupling agent and dissolved in deionized water at a ratio of 1:10. The solution is heated to 30°C-50°C, and the pH of the solution is adjusted to a range of 5.0-6.0 to make the tannic acid in the most active state, so as to form a stable chemical bond with the surface of calcium carbonate. The mixture is stirred evenly to obtain a uniform coupling solution. The pretreated calcium carbonate powder is added to the coupling solution at a ratio of 1:1, and the mixed system is heated to 30°C-50°C. The mixture is stirred for 20-40 minutes to make the tannic acid molecules evenly attached to the surface of calcium carbonate to form a stable coupling layer through hydrogen bonds and covalent bonds. The modified calcium carbonate powder is washed with deionized water until the washing liquid is colorless to remove unreacted tannic acid. The washed calcium carbonate powder is placed in an oven at 60°C-70°C for 5-7 hours to ensure that the coupling layer is stably attached and a uniform surface modification is formed.

[0053] Sodium citrate is mixed with deionized water at a ratio of 0.1:100 to form a cross-linking solution with a concentration of 0.1%, and dried coupled modified calcium carbonate powder is added to the solution. The temperature is controlled at 25°C-40°C and stirred for 20-40 minutes to allow the coupling layer to undergo a cross-linking reaction with the sodium citrate to form a stable structure. After the reaction, the calcium carbonate powder is washed 2-5 times with deionized water to remove the unreacted cross-linking agent, and the calcium carbonate powder is placed in an oven at 50°C-70°C to dry to ensure that the cross-linking layer is stable and evenly distributed;

[0054] Mixing polyethylene glycol with deionized water at a ratio of 1:10, controlling the temperature at 25°C-40°C to form a water-based treatment solution, slowly adding the cross-linked calcium carbonate powder into the water-based treatment solution, and stirring at 25°C-40°C for 30-90 minutes to uniformly coat the polyethylene glycol molecules on the particle surface, adding 5%-15% sodium citrate as a secondary cross-linking agent during the stirring process to generate stable cross-linking between the water-based coating and the coupling layer, thereby enhancing the water resistance and durability of the coating, and washing the coated calcium carbonate powder with deionized water for 2-5 times to remove the unbound treatment agent;

[0055] The coated calcium carbonate powder is placed in an oven at 50°C-70°C and dried for 6-10 hours to remove moisture and maintain the stability of the coating. After drying, the calcium carbonate powder is sieved to control the particle size to 5μm-10μm to meet the particle size requirements of different applications. The final environmentally friendly modified calcium carbonate powder is sealed in a moisture-proof bag to ensure that it is not affected by moisture during storage and transportation, maintaining its excellent surface properties and chemical stability.

[0056] Embodiment 1;

[0057] Grind the calcium carbonate powder to an average particle size of 10 μm using a grinder to ensure uniform particles of the calcium carbonate powder;

[0058] Add the ground calcium carbonate powder into deionized water at a ratio of 1:5;

[0059] In an ultrasonic dispersion device, the surface activity of calcium carbonate particles was increased and impurities were removed at a frequency of 30kHz and a power of 150W for 15 minutes;

[0060] The treated calcium carbonate powder was filtered by vacuum to remove moisture and avoid residual impurities, and then dried at 50 °C for 4 h to remove excess moisture and enhance surface activity;

[0061] Tannic acid was dissolved in deionized water at a ratio of 1:10 to form a coupling solution;

[0062] The coupling solution was heated at 30 °C and the pH was adjusted to 5.5 to ensure the activity of tannic acid;

[0063] The pre-treated calcium carbonate powder was added to the coupling solution at a ratio of 1:1 and stirred at 30°C for 30 min to allow the tannic acid molecules to be uniformly adsorbed on the surface of the calcium carbonate powder.

[0064] Use deionized water to wash several times until the washing liquid is colorless to remove excess coupling agent to avoid residual affecting subsequent treatment;

[0065] The calcium carbonate powder was placed in an oven at 50 °C and dried for 6 h to ensure that the coupling layer adhered stably and formed a uniform coating;

[0066] Dissolve 0.1 g of sodium citrate in 100 ml of deionized water to form a 0.1% cross-linking solution, and control the solution temperature at 25°C;

[0067] Add the dried calcium carbonate powder to the cross-linking solution and stir for 20 minutes to allow the coupling layer to cross-link with the sodium citrate to enhance adhesion;

[0068] Wash the calcium carbonate powder three times to remove unreacted sodium citrate and avoid cross-linking agent residue;

[0069] Dry in an oven at 60°C for 5 h to stabilize the cross-linked layer structure;

[0070] Dissolve polyethylene glycol in deionized water at a ratio of 1:10 and control the temperature at 25°C;

[0071] The cross-linked calcium carbonate powder was added to the water-based treatment solution and stirred for 60 minutes to allow the polyethylene glycol to be evenly coated on the particle surface to form a hydrophilic protective layer;

[0072] The coating was washed three times with deionized water to remove unbound treatment agent and dried at 60 °C for 8 h to ensure the stability of the coating;

[0073] Summarize;

[0074] The concentration of coupling agent and water-based treatment agent is low and the temperature is moderate. The coupling layer and water-based layer formed are thin, which is suitable for application scenarios with high lightweight requirements. Low temperature and low concentration treatment ensure the lightness and good dispersion properties of the material.

[0075] Embodiment 1;

[0076] Grind the calcium carbonate powder into an average particle size of 6 μm using a grinder;

[0077] Add calcium carbonate powder to deionized water at a ratio of 1:5;

[0078] In an ultrasonic dispersion device, the surface activity of calcium carbonate was increased and surface impurities were completely removed at 40kHz frequency and 200W power for 20 minutes.

[0079] After vacuum filtration, the powder was dried at 60 °C for 6 h to ensure the surface cleanliness of the calcium carbonate powder and enhance its activity;

[0080] Dissolve tannic acid in deionized water at a ratio of 1:10, heat to 50°C, and adjust the pH to 5.0;

[0081] The pre-treated calcium carbonate powder was added to the coupling solution at a ratio of 1:1 and stirred at 50°C for 40 min to ensure that the tannic acid was evenly attached to the surface of the calcium carbonate particles;

[0082] Wash until the washing liquid is colorless, filter and dry the calcium carbonate powder at 70°C for 7h to ensure the adhesion and stability of the coupling layer;

[0083] Dissolve sodium citrate in deionized water to form a 0.15% solution, and control the temperature at 35°C;

[0084] Add dry calcium carbonate powder to the solution and stir for 40 min to form a stable cross-linked structure;

[0085] Wash with deionized water three times to ensure that the unreacted cross-linking agent is completely removed;

[0086] The calcium carbonate powder was dried at 70°C for 6 h to ensure the firmness and durability of the cross-linked layer;

[0087] Dissolve polyethylene glycol in deionized water at a ratio of 1:10 and heat to 40°C to form a water-based solution;

[0088] Add the cross-linked calcium carbonate powder into the water-based solution and stir for 90 minutes to ensure that the water-based layer is evenly distributed;

[0089] Wash three times to remove excess polyethylene glycol and dry at 70 °C for 10 h to ensure the stability of the water-based coating;

[0090] Summarize;

[0091] High temperature and high concentration coupling agent treatment increases the thickness of the coupling layer and water-based protective layer, which is suitable for applications requiring water resistance and strength, such as plastic composites, and can show good stability in harsh chemical environments;

[0092] Embodiment 3;

[0093] Calcium carbonate powder was ground to a particle size of 8 μm and added to deionized water at a ratio of 1:5;

[0094] Ultrasonic treatment at 20kHz frequency and 120W power for 15min;

[0095] Excess water was removed by vacuum filtration and dried at 50 °C for 5 h;

[0096] Dissolve tannic acid in deionized water at a ratio of 1:10, heat to 35°C, and adjust the pH to 5.5;

[0097] Calcium carbonate powder was added to the coupling solution in a 1:1 ratio and stirred at 35°C for 20 min to allow the coupling agent to attach;

[0098] Wash with deionized water until the washing liquid is colorless, filter and dry for 6 hours;

[0099] Prepare sodium citrate solution at a ratio of 0.1:100 and control the temperature at 30°C;

[0100] Add calcium carbonate powder to the solution and stir for 30 minutes to ensure that the cross-linking reaction proceeds evenly;

[0101] Wash the calcium carbonate powder to remove unreacted products and dry it at 50°C for 4 h;

[0102] Dissolve polyethylene glycol in deionized water at a ratio of 1:15 and control the temperature at 25°C;

[0103] Calcium carbonate powder was added to the solution and stirred for 45 min to form a thin coating evenly;

[0104] Wash with deionized water, filter and dry at 50 °C for 6 h;

[0105] Summarize;

[0106] Low concentration water-based treatment agents make water-based coatings thinner and suitable for applications requiring lightness and high dispersibility, such as water-based coatings and additives.

[0107] Embodiment 4;

[0108] Use a grinder to grind calcium carbonate powder to an average particle size of 7 μm to ensure uniform particle distribution;

[0109] Add the ground calcium carbonate powder into deionized water at a ratio of 1:5;

[0110] In an ultrasonic dispersion device, ultrasonic treatment was performed at a frequency of 50 kHz and a power of 200 W for 20 min to increase the surface activity of the particles and remove impurities;

[0111] Use vacuum filtration to remove excess water and dry the calcium carbonate powder in an oven at 60°C for 4 h to ensure a clean surface and enhance the effect of subsequent treatments;

[0112] Dissolve tannic acid in deionized water at a ratio of 1:10, heat to 40°C, and adjust the pH to 5.0 to ensure the activity of tannic acid to form a coupling solution;

[0113] The pre-treated calcium carbonate powder was added to the coupling solution at a ratio of 1:1 and stirred at 40°C for 40 minutes to allow the tannic acid molecules to evenly adhere to the surface of the calcium carbonate powder.

[0114] Wash until the washing solution is colorless to remove unreacted tannic acid, and then dry the calcium carbonate powder in an oven at 60 °C for 6 h to ensure stable attachment of the coupling layer;

[0115] Sodium citrate was dissolved in deionized water at a ratio of 0.1:100 and the temperature was maintained at 40°C to form a 0.2% cross-linking solution;

[0116] Add dry calcium carbonate powder to the solution and stir for 30 min to form a stable cross-link between the coupling layer and sodium citrate;

[0117] The unreacted sodium citrate residue was removed by washing with deionized water twice, and finally the calcium carbonate powder was dried at 70 °C for 5 h to further enhance the stability of the coupling layer;

[0118] Dissolve polyethylene glycol in deionized water at a ratio of 1:10 and heat to 40°C to form a water-based treatment solution;

[0119] Add the cross-linked calcium carbonate powder into the solution and stir at 40°C for 90 minutes to ensure that the polyethylene glycol is evenly coated on the surface of the particles to form a protective layer;

[0120] The samples were washed three times with deionized water to remove excess polyethylene glycol treatment agent and dried in an oven at 70 °C for 10 h to ensure the stability of the water-based coating;

[0121] Summarize;

[0122] High concentration water-based treatment agent, with thick coating, the protective layer formed has good water resistance and weather resistance. Suitable for plastic composite materials or high filler applications with strict requirements on chemical stability.

[0123] Embodiment 5;

[0124] Grind the calcium carbonate powder into an average particle size of 6 μm using a grinder;

[0125] Calcium carbonate powder was added to deionized water at a ratio of 1:5 and treated in an ultrasonic dispersion device at a frequency of 30kHz and a power of 150W for 18 minutes to remove impurities and increase surface activity;

[0126] Use vacuum filtration to remove moisture and dry the calcium carbonate powder in an oven at 55°C for 5 h to ensure that the surface of the calcium carbonate powder is clean;

[0127] Dissolve tannic acid in deionized water at a ratio of 1:10, heat to 40°C, and adjust the pH to 5.5 to form a coupling solution;

[0128] Add calcium carbonate powder to the coupling solution in a 1:1 ratio and stir at 40°C for 30 min to ensure uniform adsorption of the coupling agent;

[0129] Wash with deionized water until the washing solution is colorless, and dry the calcium carbonate powder in an oven at 60 °C for 6 h to ensure stable attachment of the coupling layer;

[0130] Sodium citrate was dissolved in deionized water at a ratio of 0.15:100 and the temperature was controlled at 30°C to form a 0.15% cross-linking solution;

[0131] Calcium carbonate powder was added to the cross-linking solution and stirred for 30 min to allow the coupling layer and sodium citrate to form a stable cross-linking;

[0132] The samples were washed with deionized water for three times to remove the unreacted cross-linking agent, and the calcium carbonate powder was dried in an oven at 60 °C for 6 h to ensure the durability of the cross-linking layer.

[0133] Dissolve 1 g of polyethylene glycol in deionized water at a ratio of 1:10 and control the temperature at 30°C to form a water-based solution;

[0134] Calcium carbonate powder was slowly added to the water-based solution and stirred for 60 min to ensure that the water-based coating was evenly distributed on the particle surface;

[0135] After washing with deionized water and filtering to remove the unbound water-based treatment agent, it was dried in an oven at 60°C for 8 hours to finally obtain an environmentally friendly modified calcium carbonate powder with a uniform surface coating.

[0136] Summarize;

[0137] The medium temperature and medium concentration coupling and water-based treatment conditions make the coating thickness moderate, and the coupling layer and the water-based layer have good bonding strength, which is suitable for the additive requirements of many common environmental requirements;

[0138] Comparative experiment 1: Environmental pollution reduction effect

[0139] Experimental purpose: To verify the environmental advantages of the present invention in reducing the emission of harmful organic matter and heavy metal pollution by comparing unmodified calcium carbonate, traditional silane coupling agent modified calcium carbonate and different control groups of the present invention to see whether they significantly reduce the pollution to the environment;

[0140] Experimental setup;

[0141] Calcium carbonate powder samples (Examples 1-5) prepared from five different embodiments were used and compared with unmodified calcium carbonate powder and traditional chemically modified calcium carbonate powder samples. Each sample was tested for volatile organic compounds (VOCs) residues by gas chromatography-mass spectrometry (GC-MS), and the amount of organic contamination in the aqueous medium was tested by chemical oxygen demand (COD);

[0142] The experimental data are shown in Table 1:

[0143] Table 1

[0144]

[0145]

[0146] From the data in Table 1, we can get:

[0147] VOCs residue: Both the unmodified samples and the traditional chemically modified samples have high VOCs residues, while the modified samples of the five embodiments of the present invention significantly reduce the VOCs residues, especially in Examples 2 and 4, which have the lowest VOCs residues under high concentration modification conditions.

[0148] COD value: COD value reflects the amount of organic pollution in the sample in the aqueous medium. The COD values ​​of the five examples are significantly lower than those of the traditional modified and unmodified samples, and the COD values ​​of Examples 2 and 4 are the smallest, indicating that the present invention has significant advantages in environmental protection;

[0149] Comparative experiment 2: Dispersion and affinity evaluation

[0150] Experimental purpose: To evaluate the effect of the surface modification method of the present invention on the hydrophilicity, dispersibility and affinity of calcium carbonate powder;

[0151] The experiment used the modified calcium carbonate powder samples prepared in Examples 1-5 and compared them with the unmodified and traditional chemically modified samples. The test contents included:

[0152] Contact angle test: Use a contact angle meter to evaluate the hydrophilicity of the sample;

[0153] Dispersibility test: The sample was dispersed in an aqueous medium and the average particle diameter was measured by dynamic light scattering (DLS);

[0154] Sedimentation test: Place the sample in static water and observe the sedimentation height after 24 hours;

[0155] The comparative experimental data are shown in Table 2;

[0156] Table 2

[0157]

[0158] From the data in Table 2, we can get:

[0159] Contact angle: The contact angles of the modified calcium carbonate powders of Examples 1-5 are significantly lower than those of the unmodified and traditional modified samples, indicating that their hydrophilicity is significantly enhanced, among which Examples 2 and 4 have the best hydrophilicity under high concentration conditions.

[0160] Dispersibility: The average particle sizes of Examples 1-5 are all smaller than those of the traditional modified samples, indicating that the modification method of the present invention significantly improves the dispersibility, especially the high-concentration water-based treated sample of Example 4 performs best, with the smallest particle size and uniform distribution.

[0161] Sedimentation height: The sedimentation height of the samples of Examples 1-5 is significantly lower than that of the unmodified and traditional modified samples, indicating that the dispersion effect is significantly improved. In particular, the sedimentation of Examples 4 and 5 is the least, showing the best suspension stability.

[0162] Summarize;

[0163] The results of two comparative experiments show that;

[0164] Improved environmental performance: The five modification methods of the present invention significantly reduced VOCs residue and COD value, indicating its advantages in reducing environmental pollution. In particular, Examples 2 and 4 of the high-concentration coupling and water-based treatment methods performed best in terms of environmental performance.

[0165] Improved dispersibility and affinity: The modification methods of Examples 1-5 significantly improved the hydrophilicity and dispersibility of calcium carbonate powder, significantly reduced the contact angle and sedimentation height, and improved the dispersibility and stability of the particles. In particular, high-concentration coupling treatment Example 2 and high-concentration water-based treatment Example 4 had the best effects, with smaller particle sizes and higher suspension stability.

[0166] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A surface modification method for environmentally friendly calcium carbonate powder, characterized in that: The steps include: S1. Pre-treating calcium carbonate powder by ultrasonic dispersion and acid pre-treatment to remove impurities and enhance surface activity; S2, mixing the plant-derived coupling agent with deionized water at a ratio of 1:10, heating to 30°C-50°C, and adjusting the pH to 5.0-6.0 to form a coupling solution; S3, stirring and mixing the pretreated calcium carbonate powder with the coupling solution at a ratio of 1:1; S4, washing the modified calcium carbonate powder with deionized water until the washing solution is colorless, removing excess coupling solution, and drying the calcium carbonate powder in an oven to allow the tannic acid coupling layer to be stably attached; S5, performing cross-linking stabilization treatment on the calcium carbonate powder after the initial modification; S6, mixing the water-based treatment agent with deionized water at a ratio of 1:10, and controlling the temperature at 25° C.-40° C. to form a water-based treatment solution; S7, slowly adding the cross-linked calcium carbonate powder into the water-based treatment solution and stirring to form a water-based protective layer; S8. Dry, control the particle size and package the calcium carbonate powder after secondary modification to obtain environmentally friendly modified calcium carbonate powder.

2. The surface modification method of the environmentally friendly calcium carbonate powder according to claim 1, characterized in that: The step S1 specifically includes: S1.1, grind the calcium carbonate powder to control the particle size to 5μm-15μm; S1.2, mix calcium carbonate powder with deionized water in a ratio of 1:5; S1.3, place the mixed solution into an ultrasonic dispersion device at a frequency of 20kHz-50kHz and a power of 100W-200W for 15min-20min to evenly disperse the calcium carbonate powder and remove surface impurities; S1.

4. Filter the dispersed calcium carbonate powder using a vacuum filter to remove excess water; S1.5, adding citric acid to deionized water, adjusting the pH of the solution to 4.5-5.5, to obtain an acidic solution; S1.

6. Slowly add the cleaned calcium carbonate powder into the acidic solution and stir at 200-400 rpm for 10-15 min at room temperature; S1.7, wash the pretreated calcium carbonate powder with deionized water several times until the pH is neutral, and then perform vacuum filtration; S1.

8. Place the calcium carbonate powder in an oven at 50℃-70℃ and dry it for about 4h-6h.

3. The surface modification method of the environmentally friendly calcium carbonate powder according to claim 1, characterized in that: In step S2, the plant-derived coupling agent is tannic acid.

4. The surface modification method of the environmentally friendly calcium carbonate powder according to claim 1, characterized in that: In step S3, the stirring and mixing temperature is controlled at 30° C.-50° C., and the stirring time is controlled at 20 min-40 min.

5. The surface modification method of the environmentally friendly calcium carbonate powder according to claim 1, characterized in that: In step S4, the drying temperature is controlled at 60° C.-70° C., and the drying time is controlled at 5 h-7 h.

6. The surface modification method of the environmentally friendly calcium carbonate powder according to claim 1, characterized in that: The step S5 specifically includes: S5.1, mixing citric acid with deionized water in a ratio of 0.1:100 to obtain a sodium citrate solution; S5.2, adding dry calcium carbonate powder to the sodium citrate solution, stirring at 25°C-40°C for 20min-40min, so that the coupling layer and the sodium citrate undergo a cross-linking reaction; S5.3, wash the calcium carbonate powder with deionized water 2-5 times to remove unreacted sodium citrate; S5.

4. Place the calcium carbonate powder in an oven to dry, and control the drying temperature at 50°C-70°C to ensure the stability of the cross-linking layer.

7. The surface modification method of the environmentally friendly calcium carbonate powder according to claim 1, characterized in that: The water-based treatment solution in step S7 is polyethylene glycol.

8. The surface modification method of the environmentally friendly calcium carbonate powder according to claim 1, characterized in that: In step S7, the stirring time is controlled at 30 min-90 min, the temperature is controlled at 25° C.-40° C., and 5%-15% sodium citrate is added as a secondary cross-linking agent during the stirring process.

9. The surface modification method of the environmentally friendly calcium carbonate powder according to claim 1, characterized in that: In step S7, the calcium carbonate powder is washed 2-5 times with deionized water, and the modified calcium carbonate powder is collected by vacuum filtration.

10. The surface modification method of the environmentally friendly calcium carbonate powder according to claim 1, characterized in that: In the step S8, the drying temperature is controlled at 50° C.-70° C., the drying time is controlled at 6 h-10 h, and the particle size is controlled at 5 min-10 min by screening after drying.